Association of interleukin 7 receptor gene polymorphism rs6897932 with multiple sclerosis patients in Khuzestan - Majdinasab, Nastaran (Iran J Neurol, 2014)
Background: Multiple sclerosis (MS) is a chronic inflammatory demyelinating and neurodegenerative disease of central nervous system with unknown causes. Etiology of MS involves both genetic and environment factors. The interleukin 7 receptor (IL7R) gene is a promising candidate for MS, because its involvement in the autoimmunity, regulation of the T-cell homeostasis, proliferation, and anti-apoptotic signaling. Methods: We investigated the association of the IL7R gene polymorphism rs6897932 in MS patients in a case and control study. In this case and control study participating, 127 relapsing-remitting MS (RRMS) patients (mean age: 32.25, age range: 16-57) selected according McDonald criteria, and 109 ethnically, sex and age matched healthy control (mean age: 27.44, age range: 14-63) with no personal or family history of autoimmune diseases were studied. DNA was extracted from whole blood using high pure polymerase chain reaction template preparation kit from Roch Company. Amplification refractory mutation system method was applied to define the genotyping C/T within exon 6 of the IL7R gene among individuals. Results: Evaluation of the IL7R gene polymorphism revealed that the T allele and the C/T and T/T genotypes are present in 53.5%, 42.5%, 4.0%, and 68.8%, 26.6%, 4.6% in MS patients and controls, respectively. Comparison between alleles and genotypes in the MS patients and healthy controls show significant differences (P = 0.038). Conclusion: The distribution of the rs6897932 polymorphism is significantly different in our case/control study in Khuzestan Province. This single nucleotide polymorphism causes alternative splicing in exon 6 of the IL7R gene with possible influence of the autoimmunity.